Pharmaceutical composition of 1,2,4-trioxolanes with betulin in fish oil. Effect on oxidative and energy metabolism in the treatment of burns in rats - D. S. Malygina; P. V. Yastrebov; A. E. Fayans; I. V. Spitskaya; A. L. Esipovich; А. G. Soloveva; P. V. Peretyagin; N. B. Melnikova (Acta Biomedica Scientifica, 2024)
Background. Ozonation products of unsaturated fatty acids in fats and oils – 1,2,4-trioxolanes – which contribute to the normalization of oxidative and energy metabolism in various diseases, may be a promising substance for the creation of new combined anti-burn drugs.The aim. To study the effect of 1,2,4-trioxolanes in a pharmaceutical composition with betulin, which exhibits wound-healing properties, on indicators of oxidative stress and on energy metabolism in the treatment of burns in an experiment onrats. Methods. The experiments were carried out on 50 male Wistar rats with seconddegree skin burns. We assessed the activity of glutathione reductase, glucose-6-phosphate dehydrogenase, lactate dehydrogenase, aldehyde dehydrogenase, superoxide dismutase and catalase, as well as the level of lipid peroxidation indicators.Results. The properties of 1,2,4-trioxolanes were studied and a pharmaceutical composition of 1,2,4-trioxolanes with betulin from birch bark in fish oil was developed. The effect of this composition on oxidative and energy metabolism in rats during the treatment of burns was studied. The activation of NADP/H and NAD/H dependent enzymes (glutathione reductase, glucose-6-phosphate dehydrogenase, lactate dehydrogenase, aldehyde dehydrogenase), as well as superoxide dismutase and catalase, and the normalization of lipid peroxidation parameters under the influence of the studied composition in the treatment of burns were revealed. The effect of the composition on the energy metabolism of erythrocytes was noted, which was assessed by changes in the ratio of lactate dehydrogenase activity in the reverse and direct reactions. Morphohistological studies showed that using the composition under normal conditions and in case of a burn had no effect on the structure of the stomach wall, and also improved the condition of the burn wound on the day 10 compared to the wound condition in animals without treatment.Conclusion. The proposed composition of 1,2,4-trioxolanes and betulin in fish oil, which allows normalizing oxidative and energy metabolism and improving the condition of a burn wound without toxic effects on the stomach wall, can be used as an element of additional therapy in the treatment of burns.